Effect of Individual and Selected Combined Treatments With Saline Solutions and Spent Engine Oil on the Processing Attributes and Functional Quality of Tomato (Solanum lycopersicon L.) Fruit: In Memory of Professor Leila Ben Jaballah Radhouane (1958–2021) - Ilahy, Riadh; Tlili, Imen; Pék, Zoltán; Montefusco, Anna; Daood, Hussein; Azam, Mohamed; Siddiqui, Mohammed Wasim; R'him, Thouraya; Durante, Miriana; Lenucci, Marcello Salvatore; Helyes, Lajos (Frontiers in Nutrition, 2022)
The results showed that soil electrical conductivity, (EC2: 7 dS/m) increased soluble solids, lycopene content, total phenolic content, hydrophilic and lipophilic radical scavenging activities (HRSA and LRSA) by 14.2, 149, 20, 46.4, and 19.0%, respectively, compared with control. Under 0.5% spent engine oil (SEO), flavonoid content decreased by 21.7% compared with the control. HRSA and LRSA of fruits subjected to EC2/SEO1 treatment were, respectively, 45.9 and 35.5% lower than control. The a*/b* ratio was positively and significantly (P < 0.01) correlated with β-carotene (R = 0.78), lycopene (R = 0.68), total vitamin C (R = 0.71), α-tocopherol (R = 0.83), γ-tocopherol (R = 0.66), HRSA (R = 0.93), LRSA (R = 0.80), and soluble solids (R = 0.84) suggesting that it may be a promising indicator of fruit quality in areas affected by such constraints. The research revealed that combined stresses induce responses markedly different from those of individual treatments, which strain the need to focus on how the interaction between stresses may affect the functional quality of tomato fruits.